The Impact of Climate Related Risks on Financial Stability: A Global Economic and Financial Perspectives - Siregar, Inova Fitri; Ismail, Tubagus; Taqi, Muhamad; Soleha, Nurhayati (International Journal of Energy Economics and Policy, 2024)
Studies related to the influence of climate risk on financial stability have been conducted, but rarely explore the gap of how climate change, both from the transition risk, physical risk, and opportunities derived from the efficiency of resources and energy sources needed for the company. Climate-related risks have not been empirically explored or discussed to date. Institutional theory is employed to determine what factors affect the financial stability gap regarding climate-related risks. The test was conducted quantitatively with 548 samples, where the data was collected from the data of companies listed on the Indonesia Stock Exchange. The results exhibited that climate-related risk harms financial stability, while size is able to mediate the relationship between climate-related risk and financial stability. The results display increased adaptation costs or losses due to climate change, such as costs incurred to mitigate climate-related transition risks in technology, reputation, markets, and policies and regulations. The practical implication of these results is that companies must implement proactive measures to manage climate-related risks. Companies, particularly those in sectors vulnerable to climate change, such as mining, agriculture, or manufacturing, must administer resources to mitigate the negative impacts of climate risks. Meanwhile, small companies can consider cooperation and collaboration to improve their operations, which may strengthen their financial stability in facing risks.